Reversible Movement Disorder Unmasking Secondary Fahr Syndrome after Total Thyroidectomy: A Case of Bilateral Basal Ganglia and Cerebellar Calcification from Chronic Hypoparathyroidism - Made Ngurah Jiyesta Wibawa; I Putu Ananta Wijaya Sabudi (Archives of The Medicine and Case Reports, 2026)
Fahr syndrome denotes bilateral, symmetrical calcification of the basal ganglia and other deep brain structures occurring secondary to an identifiable disorder, most often hypoparathyroidism, and must be distinguished from idiopathic Fahr disease. Clinical data from Indonesia remain limited, and the movement disorder that heralds the condition is frequently mistaken for primary neurological disease. We report a 35-year-old woman who presented with a one-hour history of involuntary movements of the face and all four limbs and dysarthria from excessive facial muscle contraction, superimposed on a seven-year history of intermittent right-hand paraesthesia. Her background included a total thyroidectomy seven years earlier with subsequent levothyroxine-treated hypothyroidism, chronic hypocalcaemia presumed to reflect post-surgical hypoparathyroidism (calcium carbonate 500 mg every 12 hours), and a six-year diagnosis of “idiopathic” generalised epilepsy made without neuroimaging. Examination showed full consciousness, a positive Chvostek sign, mild four-limb ataxia and minor memory impairment. Non-contrast cranial computed tomography demonstrated multiple calcifications in both parietal lobes, the basal ganglia and both cerebellar hemispheres, without haemorrhage or infection. Serum calcium was 4.5 mg/dL and parathyroid hormone was below 6 pg/mL, confirming secondary Fahr syndrome from post-thyroidectomy hypoparathyroidism. Treatment with calcium carbonate, phenytoin, levothyroxine and vitamin B complex produced complete resolution of the involuntary movements and seizures and marked improvement of ataxia within six weeks, sustained at two months. This case underscores the need to screen phosphocalcic metabolism and obtain neuroimaging before labelling epilepsy idiopathic in any thyroidectomised patient, and the value of sustained metabolic control as both treatment and secondary prevention.